Imagining space and place: the representation of Africa through image and text in Andrew Lang's Fairy Books (1889-1910) - Womersley, Alice (African Studies, 2023)
This dissertation examines the representation of Africa and Africans in Andrew Lang's Fairy Books (1889-1910) considered to be the first global anthologies of fairy tales. Published at the heyday of the British Empire, they presented Africa and Europe alongside each other to the Victorian-era British audience of the time. As an appraisal of Lang's role as curator/editor, the study interrogates the books as containing representations of Africa from outside of Africa. While the inclusion of tales originating in Africa makes steps towards acknowledging an African story tradition independent of Europe, the editing process shaped the tales through European tale traditions and coloured by colonial perceptions of Africa. Lang's collaborative team of predominantly female translators/adaptors, as both Victorians and women, shaped the texts through their own sensitivities. The images, also created through one pictorial lens by Henry Justice Ford, were informed by imagination rather than fact, and the images were embraced for artistic merit rather than accuracy. The dissertation explores how the representation interplay and slippage between the image and text in this colonial project of ‘fairy tale' created a complex and contradictory single narrative of Africa and Africans. From this new assessment of Andrew Lang's Fairy Books (1889-1910), the dissertation formulates the argument of the cartographic imagination as fairy tale by comparing both the visual and textual components of fairy stories and maps, in addition to how they operate, how they are assembled, and their roles as agents of socialisation. These visual and textual components of fairy stories and maps were two forms of representation that were both used in the 19th century to socialise African people into being ‘productive' colonised citizens. This study models new approaches – cartographic imagination as fairy tale and the image-text relationship – to reinvestigate Victorian representations of Africa and bring a more nuanced understanding and fresh perspective to this area of scholarship.